2002
DOI: 10.1128/jb.184.7.2005-2018.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence and Analysis of the Oral Bacterium Fusobacterium nucleatum Strain ATCC 25586

Abstract: We present a complete DNA sequence and metabolic analysis of the dominant oral bacterium Fusobacterium nucleatum. Although not considered a major dental pathogen on its own, this anaerobe facilitates the aggregation and establishment of several other species including the dental pathogens Porphyromonas gingivalis and Bacteroides forsythus. The F. nucleatum strain ATCC 25586 genome was assembled from shotgun sequences and analyzed using the ERGO bioinformatics suite (http://www.integratedgenomics.com). The geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
301
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(315 citation statements)
references
References 45 publications
7
301
0
7
Order By: Relevance
“…trophozoites cultivated in the presence of 20 M of TFMET were completely lysed within 72 h. The IC 50 of TFMET (for the growth inhibition) was determined to be 18 M, which is slightly higher than that of the most commonly used antiamebic drug metronidazole [1-(2-hydroxyethyl)-2-methyl-5-nitroimidazole], which showed an IC 50 of 7 M under the same conditions (Fig. 5A).…”
Section: Table I Products Of L-methionine Degradation By the Amebic Cmentioning
confidence: 90%
See 1 more Smart Citation
“…trophozoites cultivated in the presence of 20 M of TFMET were completely lysed within 72 h. The IC 50 of TFMET (for the growth inhibition) was determined to be 18 M, which is slightly higher than that of the most commonly used antiamebic drug metronidazole [1-(2-hydroxyethyl)-2-methyl-5-nitroimidazole], which showed an IC 50 of 7 M under the same conditions (Fig. 5A).…”
Section: Table I Products Of L-methionine Degradation By the Amebic Cmentioning
confidence: 90%
“…ment of new chemotherapeutic agents against amebiasis by demonstrating an amebicidal effect of the methionine analog trifluoromethionine on trophozoites in culture (IC 50 18 M) and that this effect of trifluoromethionine was completely abolished by the addition of the MGL-specific inhibitor DL-propargylglycine.…”
mentioning
confidence: 99%
“…Following identification of the fadA gene, the genomic sequence of F. nucleatum ATCC 25586 became available (31). A BLAST search showed that the 2.4-kb fragment containing the fadA gene was highly conserved between F. nucleatum 12230 and ATCC 25586 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…ARD or CRD regions with >90 % nucleotide identity were assigned the same type designation. Seven different ARD types and eight different CRD types are present among the 64 hsdS genes ( Kapatral et al, 2002). RloA and RloB are also similar to the AbiLi and AbiLii proteins of Lactococcus lactis biovar diacetylactis plasmid pND861 (Deng et al, 1999), respectively.…”
Section: Hsd Coding Repeatsmentioning
confidence: 99%